Pengaruh Self-Efficacy Dan Work Life Balance Terhadap Kinerja Karyawan Pada KSP Delta Surya Purnama Pare - Rera Putri Rhizenda; Edy Suwasono; Heru Sutapa (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study ains to determine the influence of self-efficacy and work life balance on employee performance. Theresearch method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to employees of KSP Delta Urya Purnama Pare branch and calculated using the SPSS Version 25 application. Data analysis used included Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, and Coefficient of Determination Test . In the Validity Test, it is known that all statement items (X1, Then in the Reliability Test it was discovered that the results of the Cronbach Alpha value were > 0.60 so that the indicators for each question were declared reliable. In the t test, it is known that all items (self efficacy and work life balance) influence employee performance. Then in the F test it is known that the Sig value. for all items together it is 0.000 < 0.05 and the value of f_count > f_tabel is 13.470 > 3.28, it can be concluded that the variables self efficacy and work life balance simultaneously influence employee performance. In the Coefficient of Determination Test, it is known that the R square value is 0.449, it can be stated that X1 and X2 have an influence of 44.9%.